Circular RNA CircITGA7 Promotes Tumorigenesis of Osteosarcoma via miR-370/PIM1 Axis - Fang, Chuanwu (Comput Math Methods Med, 2020)
Many studies have shown that there are many circular RNA (circRNA) expression abnormalities in osteosarcoma (OS), and this abnormality is related to the development of osteosarcoma. But at present, it is unclear as to what circITGA7 has in the OS and what it does. In this study, qRT-PCR was used to detect the expression of circITGA7, miR-370, and PIM1 mRNA in OS tissues and cells. The CCK-8 assay was used to detect the effect of circITGA7 on cell proliferation. Later, the transwell assay was used to detect cell migration and invasion. The dual-luciferase reporter assay confirmed the existence of the targeting relationship between circITGA7 and miR-370, and miR-370 and PIM1. We found that circITGA7 was upregulated in OS tissues and cell lines. Knockdown of circITGA7 weakened the cell's ability to proliferate and metastasize. Furthermore, we observed that miR-370 was negatively regulated by circITGA7, while PIM1 was positively regulated by it. A functional assay validated that circITGA7 promoted OS progression via suppressing miR-370 and miR-370 affected OS proliferation and migration via PIM6 in OS. In summary, this study shows that circITGA7 promotes OS proliferation and metastasis via miR-370/PIM1.